2011
DOI: 10.1002/jhet.540
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted one‐pot synthesis of functionalized pyrimidines using ionic liquid

Abstract: An efficient one‐pot multicomponent synthesis of 2,4‐diamino‐5‐pyrimidinecarbonitrile derivatives has been achieved in excellent yields by the condensation of aromatic aldehydes, malononitrile, and guanidine using ionic liquid under controlled microwave irradiation (100 W) at 60°C. This green approach offers a number of advantages in terms of methodology, high‐product yield, short reaction time, mild reaction conditions, and easy workup. J. Heterocyclic Chem., (2011).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
5
1
3
Order By: Relevance
“…In contrast to earlier observations [ 32 , 33 ], we found that the reaction promoted by 10 wt.% of CS-MgO film produced 2,4-diaminopyrimidine-5-carbonitriles 1 in an excellent yield (97%) ( Scheme 2 ). The preliminary experiments confirmed that dry acetonitrile is the ideal solvent for the reaction.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to earlier observations [ 32 , 33 ], we found that the reaction promoted by 10 wt.% of CS-MgO film produced 2,4-diaminopyrimidine-5-carbonitriles 1 in an excellent yield (97%) ( Scheme 2 ). The preliminary experiments confirmed that dry acetonitrile is the ideal solvent for the reaction.…”
Section: Resultscontrasting
confidence: 99%
“…An efficient one-pot multicomponent synthesis of 2,4-diamino-5-pyrimidinecarbonitrile derivatives has been developed by the condensation of aromatic aldehydes, malononitrile, and guanidine using ionic liquid [BMIm]OH as base under microwave irradiation (100 W) at 60 °C. 214 A highly efficient synthesis of 4H-pyrano[2,3-c]pyrazoles 108 has been realized via four-component cyclocondensation of hydrazine monohydrate/phenyl hydrazine, ethyl acetoacetate, aldehydes, and malononitrile by using L-proline as catalyst in ionic liquid [BMIm]BF 4 (Scheme 61). 215 The ionic liquid could be recycled without significant loss in the reaction yields.…”
Section: Mcrs In Ionic Liquidsmentioning
confidence: 99%
“…52 Sheibani and co-workers reported another method for synthesis of this class of compounds using high-surface-area MgO as a highly effective heterogeneous base catalyst. 53 Moreover, an efficient 1-pot synthesis of 2,6-diamino-4-arylpyrimidine-5-carbonitriles 79 has been achieved in excellent yields by the condensation of malononitrile 27, aldehydes 4, and guanidinium chloride 8 using ionic liquid under controlled microwave irradiation (100 W) at 60 • C. 54 One-pot synthesis of 6-alkylamino-2,4-diaminopyrimidines 82 using ketene dithioacetals 80, 55 There are 2 more methods for synthesis of the above 2-amino-5,6-dihydropyrimidin-4(3H)-ones 61. Mohammadnejad and co-workers reported a 3-component reaction of Meldrum's acid 91, aromatic aldehyde 4, and guanidinium carbonate 6 in reflux of ethanol that leads to formation of 2-amino-5,6-dihydropyrimidin-4(3H)-ones 92.…”
Section: Meomentioning
confidence: 99%